Es-Sekkâkî'nin Miftâhu'l-Ulûm adlı eserindeki İlmu'l-İstidlâl bahsinin tahlili - Asana, Cennet (My University, 2019)
Sekkâkî, Miftâhu’l-ulûm adlı eserinin konusunu ilmu’l-edeb olarak belirlemiştir. İlmu’l-edeb, sarf, iştikâk, nahiv, meânî, beyân, bedi’, had, istidlâl, arûz ve kâfiye ilimlerinin hepsini içine alan üst bir başlık mahiyetindedir. Bu tezde söz konusu eserin üçüncü bölümünün mütemmimi olan ilmu’l-istidlâl ya da diğer adıyla ilm-i havâs-ı terâkibi’l-kelâm bahsi tahlil edilecektir. Bu bahiste ele alınan konular mantık ilmine dair meselelerdir. Bu nedenle Sekkâkî’nin ilmu’l-istidlâl bahsinde ele aldığı meseleler, sadece sistematik bir biçimde değerlendirilmemiş aynı zamanda ilmu’l-edebin içerisinde yer alan diğer ilimlerle irtibatı da ortaya konmaya çalışılmıştır. Tezin temel amacı Sekkâkî’nin ilmu’l-istidlâl bahsinde ele aldığı meseleleri tespit ve tahlil etmektir. Bu bağlamda Sekkâkî’nin ilmu’l-istidlâl bahsini neden ve nasıl ele aldığı sorularına cevap aranmıştır.

Sakkaki has determined the subject of Miftah al-ulum (The Key to the Sciences) as the knowledge of literature (ilm al-adab). Ilm al-adab is a kind of top title that includes grammar (sarf), ethymology (ishtiqaq), nahw, meanings (meani), rhetoric (beyan), aesthetic (bedii), description (had), deduction (istidlal), prosody (aruz), rhyme (kafiya). In this thesis, the chapter of ilm al-istidlal -also known as ilm-i havâs-i terakibi’l-kelâm- which is the complementary of the third section of work (Miftah al-ulum) will be analized. In this chapter the topics are related to the knowledge of logic. For this reason, the topics that Sakkaki deal with it in the chapter of ilm al-istidlal are not only analized systematicly, but also tried to find out its conection with other knowledges in ilm al-adab. The aim of the thesis is to identify ad analyze the issues in ilm’ul istidlal. In this context, questions concerning why and how Sakkaki handled the chapter of ilm al-istidlal were discussed.
Keywords: belâgat; deduction (istidlal); dil-mantık; istidlâl; language-logic; Miftah al-ulum; Miftâhu’l-ulûm; rhtetoric; Sakkaki; Sekkâkî